The Ideal Model of Law Education to Achieve Progressive Law Enforcement - Sudiyana, Sudiyana (The Indonesian Journal of International Clinical Legal Education, 2019)
The legal education in Indonesia tends to produce graduates whobelieve in legal positivism. The principle of legal positivism runs asfollows. Firstly, it encourages law enforcers to think and act in any legalformalistic way. Secondly, it places judges as the mouthpiece of the law;who cannot express to make decisions that satisfy a sense of socialjustice and substantive justice. How the ideal model of legal educationis formed in order to create more progressive law enforcement. Thisarticle is based on the socio-juridical approach by underlying theanalysis of the law and regulations which are related to the applicationof legal education in the community. The legal education is oriented tolegal positivism that results in law enforcement with the understandingof law based on the abstract values, not on the values that live andthrive in society, so that the understanding of the law in a legal sense ismore repressive, and not responsive. Law is understood as unfunctionaland un-pragmatic things therefore understanding of law isthe law that merely protects the elite group of citizens, in such a waythat equality before the law and the rule of law don’t work. Legaleducation in the future should be based on the sociological aspects ofprioritizing the principles of social justice and the benefits for thecommunity, instead of legal certainty only. Legal education will producea responsive law enforcement that put substantive fairness and socialjustice as a legal purpose.